3D printing of gear-inspired biomaterials: Immunomodulation and bone regeneration. (15th January 2023) - Yu, Xiaopeng; Wang, Yufeng; Zhang, Meng; Ma, Hongshi; Feng, Chun; Zhang, Bingjun; Wang, Xin; Ma, Bing; Yao, Qingqiang; Wu, Chengtie
Abstract: It is of significance to construct the immunomodulatory and osteogenic microenvironment for three dimension (3D) regeneration of bone tissues. 3D scaffolds, with various chemical composition, macroporous structure and surface characteristics offer a beneficial microenvironment for bone tissue regeneration. However, there is a gap between the well-ordered surface microstructure of bioceramic scaffolds and immune microenvironment for bone regeneration. In this study, a gear-inspired 3D scaffold with well-ordered surface microstructure was successfully prepared through a modified extrusion-based 3D printing strategy for immunomodulation and bone regeneration. The prepared gear-inspired scaffolds could induce M2 phenotype polarization of macrophages and further promoted osteogenic differentiation of bone mesenchymal stem cells in vitro . The subsequent in vivo study demonstrated that the gear-inspired scaffolds were able to attenuate inflammation and further promote new bone formation. The study develops a facile strategy to construct well-ordered surface microstructure which plays a key role in 3D immunomodulatory and osteogenic microenvironment for bone tissue engineering and regenerative medicine. Statement of significance: A gear-inspired 3D bioceramic scaffold with highly well-ordered surface microstructure was successfully fabricated through a modified extrusion-based 3D printing technique. The size and shape of the highly well-ordered microstructure could be readily modulated. Taking advantage of good inducing effect of the well-ordered microstructure, the gear-inspired scaffold could be used as a satisfactory biomaterial, which could induce M2 phenotype polarization of macrophages and further promoted osteogenic differentiation of bone mesenchymal stem cells in vitro . The gear-inspired scaffold could construct 3D immunomodulatory microenvironment to significantly attenuate inflammation and further promote new bone formation in vivo . Graphical abstract: Image, graphical abstract